2016
DOI: 10.1007/s13199-016-0395-x
|View full text |Cite
|
Sign up to set email alerts
|

Decapod crustacean associations with scyphozoan jellyfish (Rhizostomeae: Pelagiidae) in the Southeastern Brazilian coast

Abstract: In southeastern Brazil, decapod crustaceans were found living in association with the scyphozoan jellyfish. In total, 2002 specimens of the Scyphozoa Lychnorhiza lucerna were collected of which 511 were associated decapods that were identified as three species of the crab Libinia ferreirae, Libinia spinosa, and one Grapsoidea sp. and two species of caridean shrimps Periclimenes paivai and Leander paulensis. This is the first record of an association between the caridean shrimp L. paulensis and a scyphozoan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…The random population distribution of P. paivai on the jellyfish L. lucerna agrees with that reported for other ectosymbiotic crustaceans that are not territorial and live in aggregations on their host individuals (caridean shrimps: Ancylomenes pedersoni (Chace, 1958) [52], Periclimenes antipathophilus Spotte, Heard & Bubucis, 1994 [53], Periclimenes patae Heard & Spotte, 1991 [54] and Thor amboinensis [18]; other crustaceans: Petrolisthes mitra [6], and Dissodactylus primitivus Bouvier, 1917 [21]). Our observations also agree with previous studies conducted in other localities that have reported P. paivai living gregariously on the surface of the same or a different host species (e.g., [33,34]). By contrast to that observed in P. paivai, territorial species display a uniform population distribution and live solitarily (or in male-female pairs) in/on their respective host species with a frequency greater than expected by chance alone [25,27,55].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The random population distribution of P. paivai on the jellyfish L. lucerna agrees with that reported for other ectosymbiotic crustaceans that are not territorial and live in aggregations on their host individuals (caridean shrimps: Ancylomenes pedersoni (Chace, 1958) [52], Periclimenes antipathophilus Spotte, Heard & Bubucis, 1994 [53], Periclimenes patae Heard & Spotte, 1991 [54] and Thor amboinensis [18]; other crustaceans: Petrolisthes mitra [6], and Dissodactylus primitivus Bouvier, 1917 [21]). Our observations also agree with previous studies conducted in other localities that have reported P. paivai living gregariously on the surface of the same or a different host species (e.g., [33,34]). By contrast to that observed in P. paivai, territorial species display a uniform population distribution and live solitarily (or in male-female pairs) in/on their respective host species with a frequency greater than expected by chance alone [25,27,55].…”
Section: Discussionsupporting
confidence: 93%
“…Periclimenes paivai is a small shrimp (maximum size = 9.2 mm CL [carapace length]- [32][33][34]), endemic to the western Atlantic coast, and is restricted to shallow waters from Rio de Janeiro to Santa Catarina, Brazil [35,36]. Periclimenes paivai has been considered a facultative commensal shrimp [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, studies on this spider crab L. ferreirae have addressed their larval development (Anger et al, 1989;Bakker et al, 1990), symbiotic relationships (Nogueira Jr. and Haddad, 2005;Winter and Masunari, 2006;Gonçalves et al, 2016;2017b), morphology and maturity (Tavares and Santana, 2012;Gonçalves et al, 2017a) and distribution (Braga et al, 2007). However, little is known about the growth of this species.…”
Section: Spider Crab's Growthmentioning
confidence: 99%